Partisipasi Masyarakat pada Kegiatan Lomba Mewarnai dan Balap Karung di Kelurahan Pohe - Abdi Gunawan Djafar; Rahmayanti Rahmayanti; Sri Janiansi Gaib; Syafrudin Karim (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
The Pantai Indah Pohe tourist area in Pohe Village, Gorontalo City, holds significant potential as a premier coastal tourism destination. However, challenges such as a lack of adequate location markers and insufficient visual promotion strategies hinder its development. To address these issues, a community service initiative was carried out by the D4 Architecture and Building Construction (ABG) Program at Gorontalo State University. The initiative aimed to enhance the visual image of the area and foster greater community involvement in promoting local tourism. The project adopted a participatory approach, actively engaging the village government, tourism awareness groups, and residents of various age groups. The activities involved creating and installing a new signage system for the "Pantai Indah Pohe" area, which serves as a crucial element for enhancing the visibility of the tourist spot. In addition, community engagement was facilitated through events such as coloring contests and sack races, aimed at promoting a sense of unity and local pride. The outcomes of this initiative revealed an increase in community awareness regarding the importance of visual promotion for tourism. It also fostered stronger social connections between local residents and academics, contributing to the community’s sense of ownership and pride in their local resources. Furthermore, the initiative provided tangible contributions to the strengthening of the local identity, with community members actively participating in the improvement process. The project aligns with Community-Based Tourism (CBT) principles and placemaking theory, which emphasize the importance of community involvement in shaping tourist destinations. This community service activity serves as an exemplary model of integrating architectural design, education, and sustainable tourism development, showcasing how academic and community collaboration can drive positive changes in local tourism promotion.